Teacher Education in Professional Learning Communities Lessons from the Reciprocal Learning Project - Huang, Xuefeng (Intercultural Reciprocal Learning in Chinese and Western Education, 2018)
This book explores the unique experiences of a sister school network in Canada and China contextualized through the lens of the Reciprocal Learning Project, which supports the relationship between a school network and teacher education exchange program of two countries. Huang uses theoretical viewpoints from teacher learning and comparative education research to analyse and interpret what has happened in the emerging cross-cultural school network. The book juxtaposes teacher learning and comparative education research from Shanghai and Ontario as teachers in the two places interact and provides detailed descriptions of teacher collaboration to show how these collaborations were initiated, developed, and sustained, as well as the impact brought about from these collaborations. The book offers a unique opportunity to examine how Canadian and Chinese teachers receive and react to opportunities of cross-cultural collaboration and learning.